Analisis Pengaruh Hari Perdagangan dan Nilai Tukar terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia Tahun 2009 - Erric Wijaya; Fatiah Istarini (Bina Nusantara University, 2011)
Before making investment decisions, investors need to analyze the pattern of trading days which change daily because of investors’ behavior in stock trading activity that affects the pattern of daily stock price movements. Changes in macro variables like exchange rates for instance, also can affect share price. To determine the influence of independent variables (day of the week effect and exchange rate) on the dependent variable (Jakarta Composite Index (JCI)), a research is conducted using multiple linear regression analysis. The initial test uses a test of normality and is resumed by testing multiple linear regression analysis and classical assumption. The hypothesis test uses t-statistics and F-statistics with a significance level of 5%. A descriptive statistics implies that there is an effect of trading days on stock prices. However, using backward stepwise linier regression model and multivariate analysis, the result indicates that there is no effect of trading days on stock prices. Using multivariate data analysis, it is found that stock prices is influenced by exchange rate.